KONSISTENSI PENGATURAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERUSAHAAN DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Vanessha Dasenta Demokracia (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
The article aims to find out and examine the inconsistencies in the regulation of corporate social and environmental responsibility in Indonesian laws and regulations and the legal politics of corporate social and environmental responsibility in Indonesian laws and regulations. This research is normative research with a legal political approach. The data source is in the form of secondary data consisting of primary legal materials and secondary legal materials. Methods of data collection using literature and interviews. Primary legal materials and secondary legal materials were analyzed using legal analysis methods. The thinking process used to draw conclusions is the deductive thinking process. There are inconsistencies in the regulation of corporate social and environmental responsibility in Indonesia, especially in Law Number 25 of 2007 concerning Investment and Law Number 40 of 2007 concerning Limited Liability Companies. There is an inconsistency or discrepancy in the regulation of corporate social and environmental responsibility because there is a discrepancy in the concept of corporate social and environmental responsibility in several laws that regulate this matter. Arrangements regarding social and environmental responsibility in Indonesia should be developed to address the current issues of corporate social and environmental responsibility. Renewal of social and environmental responsibility regulations can be carried out by taking into account the legal system and legal principles in force in Indonesia. This will enable the creation of legal certainty and provide justice for the parties in the implementation of corporate social and environmental responsibility.